The view of the conquered in the Andean Culture - Carranza Elguera, Víctor (2021)
This project aims to evaluate the different positions adopted by indigenous elite in order to explain and justify the political, economic and cultural changes that came up after the Spanish conquest of the Tawantinsuyo. The realization of this project was based on the hermeneutic methodology with the purpose of interpreting the Andean historical and social context from the most representative authors’ books and works. In this regard, the accusations of political oppression and cultural alienation suffered by indigenous people, systematized by Guamán Poma de Ayala, and the integration proposal of the Andean and Spanish civilization through cultural miscegenation developed by Inca Garcilaso de la Vega are highlighted.